2010
DOI: 10.1186/1471-244x-10-85
|View full text |Cite
|
Sign up to set email alerts
|

Simulation studies of age-specific lifetime major depression prevalence

Abstract: BackgroundThe lifetime prevalence (LTP) of Major Depressive Disorder (MDD) is the proportion of a population having met criteria for MDD during their life up to the time of assessment. Expectation holds that LTP should increase with age, but this has not usually been observed. Instead, LTP typically increases in the teenage years and twenties, stabilizes in adulthood and then begins to decline in middle age. Proposed explanations for this pattern include: a cohort effect (increasing incidence in more recent bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…In many studies, lifetime prevalence has been reported to decline with age, which has sometimes been interpreted as a birth cohort effect. Although multiple factors may contribute to the pattern, including differential mortality, these results corroborate previous studies indicating that recall bias is likely to be an important part of the explanation [19,20]. Lifetime prevalence may appear to diminish with age because episodes occurring earlier in life are not recalled by older survey respondents.…”
Section: Discussionsupporting
confidence: 79%
“…In many studies, lifetime prevalence has been reported to decline with age, which has sometimes been interpreted as a birth cohort effect. Although multiple factors may contribute to the pattern, including differential mortality, these results corroborate previous studies indicating that recall bias is likely to be an important part of the explanation [19,20]. Lifetime prevalence may appear to diminish with age because episodes occurring earlier in life are not recalled by older survey respondents.…”
Section: Discussionsupporting
confidence: 79%
“…One recent report has suggested that the pattern of lifetime prevalence observed in crosssectional epidemiologic studies seems most plausibly explained by incidence that declines with age. They concluded that a cohort effect was not a necessary interpretation of the observed pattern of age-specific lifetime prevalence [38]. Prospective longitudinal studies are therefore needed to confirm if such an increase in prevalence among younger cohorts is real.…”
Section: Study Limitationsmentioning
confidence: 99%
“…More and more different groups in the societies suffer from depression. The age boundaries of this illness widen among the elderly people (Büchtemann et al, 2012;Bose & Neelakandan, 2013;Wood et al, 2010) and youth (Tezvaran, Akan, & Zahmaciog, 2012;Cole et al, 2012), but depression is more typical for the people advanced in age (about 50 years old) than for the young people (Wood et al, 2010;Patten, Gordon-Brown, & Meadows, 2010). The representatives of different kinds of occupations also experience this disorder in some moment of their life-even the doctors (Galán-Rodas et al, 2011).…”
Section: Human Health Is Among the Most Important Values In All Sociementioning
confidence: 99%